The Effect of Fiscal Independence and Economic Growth on Reducing Poverty and Unemployment in Indonesia - Amin, Arif; Bambang Juanda; Wiwiek Rindayati (Economics, Business, Accounting & Society Review, 2023)
Fiscal independence affects the revenue and expenditure patterns of a local government which in turn affects economic growth and can reduce poverty and unemployment. This study was conducted in 33 provinces in Indonesia using secondary data with a time span from 2013 to 2019. The model used is a dynamic simultaneous panel model with the SYS-GMM approach. Besides that, there is a need to develop fiscal independence index to obtain clearer conditions for fiscal independence. Revenue Sharing Fund variable that is not included in the calculation. Revenue Sharing Fund is a source of income that is already generated by a region. Readjustments are needed by including revenue sharing funds in the calculation. The newly developed fiscal independence index more clearly describes the condition. Riau, Lampung and South Sulawesi were included in the independence fiscal region category that was not previously. Fiscal independence has a significant effect and positive relationship with GRDP. Meanwhile, the reduced form results on poverty and unemployment show that GRDP has a significant negative effect on poverty and unemployment. Fiscally independent regions are better at reducing poverty and unemployment.